МАКЕДОНСКАТА КНИЖЕВНА КРИТИКА ОД XIX ВЕК ЗА ДЕЛОТО НА ГРИГОР ПРЛИЧЕВ - Славчо Ковилоски (Универзитет „Гоце Делчев“, Филолошки факултет, Штип, 2024)
n this paper we refer to the echo of Grigor Prlichev’s work in the Macedonian literary criticism from the 19th century. As a leader of Macedonian literature, Prlichev impressed the Macedonian literary figures of this time. Some of them were his collaborators, some were his students, whereas others knew him only through his poetic work, but they all had exceptional respect not only for his literary legacy, but for his involvement in the field of education and church struggle as well. In this paper we present to the wider Macedonian audience the views and criticism on the poet from Ohrid of the Macedonian authors Jordan Ivanov, Georgi Balaschev, Kuzman Shapkarev, Dimitar Matov, Kliment Skopakov and Lev Ognenov.
Keywords: Grigor Prlichev; Macedonian literature of the 19th century; literary criticism.